Eosinophilic esophagitis: clinical, endoscopic, histologic and therapeutic differences and similarities between children and adults. (January 2021) - Visaggi, Pierfrancesco; Savarino, Edoardo; Sciume, Giusi; Chio, Teresa Di; Bronzini, Francesco; Tolone, Salvatore; Frazzoni, Marzio; Pugno, Camilla; Ghisa, Matteo; Bertani, Lorenzo; Bellini, Massimo; Savarino, Vincenzo; et al.
In the absence of secondary causes, eosinophilic esophagitis (EoE) is a chronic, local, progressive, T-helper type 2 immune-mediated disorder characterized by symptoms of esophageal dysfunction and eosinophil-predominant inflammation. In the last 20 years, the incidence and prevalence of EoE have risen sharply, and the chances of encountering affected patients in clinics and endoscopy rooms have increased. Nevertheless, it is estimated that the mean diagnostic delay of EoE is 4–6 years in both children and adults. Unfortunately, the longer the disease stays unrecognized, the likelier it is for the patient to have persistent or increased esophageal eosinophilic inflammation, to complain of non-resolving symptoms, and to develop fibrotic complications. Early detection depends on the recognition of initial clinical manifestations that vary from childhood to adulthood and even among patients of the same age. The disease phenotype also influences therapeutic approaches that include drugs, dietary interventions, and esophageal dilation. We have herein reviewed epidemiologic, clinical, endoscopic, and histologic features and therapeutic options of EoE focusing on differences and similarities between children and adults that may certainly serve in daily clinical practice.